Functional dyspepsia and gut microbiome - H. Mori; M. Sano; H. Suzuki (Microbiota in Health and Disease)
The definitive pathophysiology of functional dyspepsia remains unclear, and effective treatments are limited. Among the mechanisms assumed to be involved in its pathogenesis, duodenal low-grade inflammation has received the most attention. Emerging evidence suggests that the oral microbiome, such as Streptococcus spp., may play a role in gastroduodenal motility and low-grade duodenal inflammation. In terms of treatment, traditional treatments, such as herbal medicine, are showing changes in the intestinal microbiome and its metabolites. In other words, both old and new evidence are being progressively revealed.